Potential Molecular Targets of Tenofovir Disoproxil Fumarate for Alleviating Chronic Liver Diseases via a Non-Antiviral Effect in a Normal Mouse Model - Duan, Yuanqin; Chen, Zhiwei; Li, Hu; Shen, Wei; Zeng, Yi; Peng, Mingli; Hu, Peng (Frontiers in Molecular Biosciences, 2021)
Accumulating evidence suggests that tenofovir disoproxil fumarate (TDF) can attenuate liver fibrosis directly, the mechanism of which, however, has not been fully elucidated, and there is a paucity of data concerning whether TDF can also mitigate other chronic liver diseases (CLDs). We aimed to identify the molecular targets and potential mechanism of TDF itself in ameliorating CLDs. RNA-sequencing was performed on mouse liver tissues treated with TDF or normal saline. Then, the differentially expressed genes (DEGs) were screened, and enrichment analyses of the function and signaling pathways of DEGs were done with Database for Annotation, Visualization and Integrated Discovery (DAVID) and Metascape. Next, protein-protein interaction (PPI) networks were constructed and module analyses were utilized to identify significant genes. Subsequently, the DisGeNET platform was used to identify the potential target genes of TDF in mitigating these diseases. Finally, prediction of the transcription factors (TFs) and microRNAs (miRNAs) of the target genes was done to conjecture the underlying mechanism by which TDF relieved CLDs. As a result, a total of 854 DEGs were identified, and the DEGs were involved mainly in “immunity”, “inflammation” and “metabolism” process. In addition, fifty significant genes were obtained via PPI construction and module analyses. Furthermore, by means of DisGeNET, 19 genes (Adra2a, Cxcl1, Itgam, Cxcl2, Ccr1, Ccl5, Cxcl5, Fabp5, Sell, Lilr4b, Ccr2, Tlr2, Lilrb4a, Tnf, Itgb2, Lgals3, Cxcr4, Sucnr1, Mme) were identified to be associated with nine CLDs. Finally, 34 miRNAs (especially mmu-miR-155-5p) and 12 TFs (especially Nfkb1) were predicted to be upstream of the nine target genes (Cxcl1, Cxcl2, Ccl5, Ccr2, Sell, Tlr2, Tnf, Cxcr4, Mme) of TDF in ameliorating CLDs. In conclusion, our study suggests that TDF have the potential to ameliorate CLDs independently of its antiviral activity by affecting the expression of genes involved in hepatic immune, inflammatory, and metabolic processes via mmu-miR-155-5p-NF-κB signaling. These findings provided prima facie evidence for using TDF in CHB patients with concurrent CLDs.